Triterpene and sterols from Hoya pubicalyx Merr - Panahon, Nelson M. (Animo Repository, 2016)
Chemical investigation of the dichloromethane extract of the leaves of Hoya pubicalyx Merr. yielded taraxerol (1), β-sitosterol (2) and stigmasterol (3). The structures of 1-3 were identified by comparison of their NMR data with those reported in the literature.